Seismic Progressive Collapse: Qualitative Point of View - H. Wibowo; D. T. Lau (Institute of Research and Community Outreach - Petra Christian University, 2009)
Progressive collapse is a catastrophic structural phenomenon that can occur because of human-made and natural hazards. In progressive collapse mechanism, a single local failure may cause a significant deformation which then may lead to collapse of a structure. The current practices in progressive collapse analysis and design method generally focus on preventing progressive collapse due to abnormal gravity and blast loads. Progressive collapse behaviour of structures due to earthquake loads has not received as much attention. This paper presents a brief overview of the current state-of-knowledge, insights, and issues related to progressive collapse behaviour of structures caused by earthquake loading.